Simple Linear Equations, But Introducing Floors!

Algebra Level 5

2 x + 1 3 + 4 x + 5 6 = 3 x 1 2 \large{\left \lfloor \dfrac{2x+1}{3} \right \rfloor + \left \lfloor \dfrac{4x+5}{6} \right \rfloor = \dfrac{3x-1}{2}}

Find the sum of all real x {x} satisfying the above equation.


The answer is 39.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Satyajit Mohanty
Jul 29, 2015

Since 2 x + 1 3 + 4 x + 5 6 \left \lfloor \dfrac{2x+1}{3} \right \rfloor + \left \lfloor \dfrac{4x+5}{6} \right \rfloor is an integer, so 3 x 1 2 \dfrac{3x-1}{2} must also be an integer.

Let x = 2 n + 1 3 x= \dfrac{2n+1}{3} for some integer n n . .... (1) \text{ .... (1)}

We'll also use the fact that:

2 x + 1 3 + 1 2 = 4 x + 5 6 .... (2) \dfrac{2x+1}{3} + \dfrac12 = \dfrac{4x+5}{6} \text{ .... (2)}

For every real number α \alpha , we have:

α α < 1 2 ( α + 1 2 ) α + 1 2 1 2 \alpha - \lfloor \alpha \rfloor < \dfrac12 \Rightarrow \left( \alpha + \dfrac12 \right) - \left \lfloor \alpha + \dfrac12 \right \rfloor \geq \dfrac12

[that is, the fractional part of α < 1 / 2 \alpha < 1/2 if and only if the fractional part of α + 1 / 2 1 / 2 \alpha + 1/2 \geq 1/2 ] so that

α > α 1 2 α + 1 2 α \left \lfloor \alpha \right \rfloor > \alpha - \dfrac12 \Rightarrow \left \lfloor \alpha + \dfrac12 \right \rfloor \leq \alpha

From this, using y y \left \lfloor y \right \rfloor \leq y , we obtain:

α + α + 1 2 2 α ....(3) \left \lfloor \alpha \right \rfloor + \left \lfloor \alpha + \dfrac12 \right \rfloor \leq 2\alpha \text{ ....(3)}

And using y > y 1 \left \lfloor y \right \rfloor > y-1 we obtain:

α + α + 1 2 > 2 α 1 ....(4) \left \lfloor \alpha \right \rfloor + \left \lfloor \alpha + \dfrac12 \right \rfloor > 2\alpha - 1 \text{ ....(4)}

both for every real number α \alpha .

Putting inequalities (3) and (4) together and using (2) gives, for α = 2 x + 1 3 \alpha = \dfrac{2x+1}{3} :

2 ( 2 x + 1 ) 3 1 < 2 x + 1 3 + 4 x + 5 6 2 ( 2 x + 1 ) 3 \dfrac{2(2x+1)}{3} - 1 < \left \lfloor \dfrac{2x+1}{3} \right \rfloor + \left \lfloor \dfrac{4x+5}{6} \right \rfloor \leq \dfrac{2(2x+1)}{3}

Using the original equation, this is:

4 x 1 3 < 3 x 1 2 4 x + 2 3 \dfrac{4x-1}{3} < \dfrac{3x-1}{2} \leq \dfrac{4x+2}{3} .

From this we obtain 1 < x 7 1 < x \leq 7 . Using (1) the only possibilities are:

x = 5 3 , 7 3 , 9 3 , , 21 3 x = \dfrac53, \dfrac73, \dfrac93, \ldots, \dfrac{21}{3}

This is exactly the set of all solutions, and their sum being 39 \boxed{39} .

x = 1 x=1 satisfies the equation.

Miloje Đukanović - 5 years, 8 months ago

Log in to reply

No it does not. Check again

Ishan Tarunesh - 5 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...